New horizons for caring for people with dementia in hospital: the DEMENTIA CARE pointers for service change - Abbott, R. A.; Rogers, M.; Lourida, I.; Green, C.; Ball, S.; Hemsley, A.; Cheeseman, D.; Clare, L.; Moore, D.; Hussey, C.; Coxon, G.; Llewellyn, D. J.; et al. (Age and Ageing, 2022)
Approximately two-thirds of hospital admissions are older adults and almost half of these are likely to have some form of dementia. People with dementia are not only at an increased risk of adverse outcomes once admitted, but the unfamiliar environment and routinised practices of the wards and acute care can be particularly challenging for them, heightening their confusion, agitation and distress further impacting the ability to optimise their care. It is well established that a person-centred care approach helps alleviate some of the unfamiliar stress but how to embed this in the acute-care setting remains a challenge. In this article, we highlight the challenges that have been recognised in this area and put forward a set of evidence-based 'pointers for service change' to help organisations in the delivery of person-centred care. The DEMENTIA CARE pointers cover areas of: dementia awareness and understanding, education and training, modelling of person-centred care by clinical leaders, adapting the environment, teamwork (not being alone), taking the time to 'get to know', information sharing, access to necessary resources, communication, involving family (ask family), raising the profile of dementia care, and engaging volunteers. The pointers extend previous guidance, by recognising the importance of ward cultures that prioritise dementia care and institutional support that actively seeks to raise the profile of dementia care. The pointers provide a range of simple to more complex actions or areas for hospitals to help implement person-centred care approaches; however, embedding them within the organisational cultures of hospitals is the next challenge. Published version, accepted version (12 month embargo), submitted version The article is available via Open Access. Click on the 'Additional link' above to access the full-text.